Writing the past, inscribing the future history as prophesy in colonial Java - Florida, Nancy K. (Duke University Press, 1995)
Located at the juncture of literature, history, and anthropology, Writing the Past, Inscribing the Future charts a strategy of how one might read a traditional text of non-Western historical literature in order to generate, with it, an opening for the future. This book does so by taking seriously a haunting work of historical prophecy inscribed in the nineteenth century by a royal Javanese exile-working through this writing of a colonized past to suggest the reconfiguration of the postcolonial future that this history itself apparently intends. After introducing the colonial and postcolonial orientalist projects that would fix the meaning of traditional writing in Java, Nancy K. Florida provides a nuanced translation of this particular traditional history, a history composed in poetry as the dream of a mysterious exile. She then undertakes a richly textured reading of the poem that discloses how it manages to escape the fixing of "tradition." Adopting a dialogic strategy of reading, Florida writes to extend-as the work's Javanese author demands-this history's prophetic potential into a more global register